The critical response to Robert Musil's The man without qualities - Mehigan, Tim 1960- (Boydell & Brewer, 2003)
The Austrian writer Robert Musil ranks among the foremost novelists of the 20th century. Despite a series of lesser but well-regarded shorter works, his literary reputation rests almost entirely on his novel 'Der Mann ohne Eigenschaften' (The Man without Qualities), a life-work in the truest sense, which became the focus of all his energies and thinking from 1924 until his death in 1942. This study analyzes the principal trends in scholarship on the novel from the 1960s to the present. It contrasts earlier criticism, which foregrounded the eponymous central character's search for identity against the background of subject theory or mysticism, with more recent criticism, which has focused on aesthetic and ethical approaches to the novel within the broader context of theories of value. A focal chapter in the study centers on the persistent difficulty critics have encountered with the idea of 'Eigenschaftslosigkeit', the state of being without qualities named in the novel's title. Tim Mehigan is Associate Professor of German and Head of the Department of Germanic Studies and Russian at the University of Melbourne